Pengaruh Tingkat Pendidikan, Pengetahuan Akuntansi, dan Pelatihan Akuntansi Terhadap Penggunaan Informasi Akuntansi pada UMKM (di Kecamatan Makasar Jakarta Timur) - Syifaurrohman, Mochammad Angga; Perdana, Petrolis Nusa; Susanti, Santi (LPPM Universitas Negeri Jakarta, 2023)
The purpose of this study is to determine how education level, accounting knowledge, and accounting training impact the usage of accounting information in Micro, Small, and Medium Enterprises (MSMEs) in Makasar District, East Jakarta. This analysis includes MSME owners from Makasar District who have registered on the JakPreneur platform and correspond to the specified sample. This study employs a non-probability sampling strategy with the Purposive Sampling type and the Convenience aSampling technique. For this study, we performed inferential analysis using SmartPls 3. According to the findings, accounting expertise has a favorable influence on the utilization of accounting information in MSMEs, however education level has a negative impact. Accounting training has a detrimental influence on how MSMEs use accounting information. Based on these findings, future researchers are advised to increase the sample of MSMEs utilized as respondents and investigate additional characteristics that may impact the usage of accounting data.